GDNF Gene Therapy to Repair the Injured Peripheral Nerve - Eggers, Ruben; de Winter, Fred; Tannemaat, Martijn R.; Malessy, Martijn J. A.; Verhaagen, Joost (Frontiers in Bioengineering and Biotechnology, 2020)
A spinal root avulsion is the most severe proximal peripheral nerve lesion possible. Avulsion of ventral root filaments disconnects spinal motoneurons from their target muscles, resulting in complete paralysis. In patients that undergo brachial plexus nerve repair, axonal regeneration is a slow process. It takes months or even years to bridge the distance from the lesion site to the distal targets located in the forearm. Following ventral root avulsion, without additional pharmacological or surgical treatments, progressive death of motoneurons occurs within 2 weeks (Koliatsos et al., 1994). Reimplantation of the avulsed ventral root or peripheral nerve graft can act as a conduit for regenerating axons and increases motoneuron survival (Chai et al., 2000). However, this beneficial effect is transient. Combined with protracted and poor long-distance axonal regeneration, this results in permanent function loss. To overcome motoneuron death and improve functional recovery, several promising intervention strategies are being developed. Here, we focus on GDNF gene-therapy. We first introduce the experimental ventral root avulsion model and discuss its value as a proxy to study clinical neurotmetic nerve lesions. Second, we discuss our recent studies showing that GDNF gene-therapy is a powerful strategy to promote long-term motoneuron survival and improve function when target muscle reinnervation occurs within a critical post-lesion period. Based upon these observations, we discuss the influence of timing of the intervention, and of the duration, concentration and location of GDNF delivery on functional outcome. Finally, we provide a perspective on future research directions to realize functional recovery using gene therapy.